2021
DOI: 10.5713/ab.20.0550
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin supplementation enriches productive performance, physiological and immunological responses in laying hens

Abstract: Objective: Astaxanthin is a natural super antioxidant. The present study was carried out to investigate the effect of astaxanthin rich Phaffia rhodozyma (PR) supplementation in diet on laying production performance, egg quality, antioxidant defenses and immune defenses in laying hens. Methods: A total of five hundred and twelve 60-week-old Lohmann Brown laying hens (2243±12 g) were randomly assigned to four groups, each including 4 replicates with 32 birds per replicate. Astaxanthin rich PR was added to corn-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…Oxidative stress can increase DNA fragmentation, causing an increase in the mutagenesis content of 8hydroxy-2-deoxyguanosine (8-OH-2-dG) (Sudharshan and Dyavaiah 2021). Astaxanthin can prevent or reduce the oxidation of guanosine (Zhu et al 2021). Subsequently, adding lactose-astaxanthin combination to egg yolk phosphate diluent for storage of Green junglefowl semen at 5 o C maintained progressive motility and reduced DNA fragmentation (Bebas et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress can increase DNA fragmentation, causing an increase in the mutagenesis content of 8hydroxy-2-deoxyguanosine (8-OH-2-dG) (Sudharshan and Dyavaiah 2021). Astaxanthin can prevent or reduce the oxidation of guanosine (Zhu et al 2021). Subsequently, adding lactose-astaxanthin combination to egg yolk phosphate diluent for storage of Green junglefowl semen at 5 o C maintained progressive motility and reduced DNA fragmentation (Bebas et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…On egg performance, research by Zhu et al [ 45 ] showed that AST-rich P. rhodozyma could improve egg yolk color. Yolk discoloration is also found in other carotenoids [ 46 ].…”
Section: Dietary Intake Levels Of Astaxanthinmentioning
confidence: 99%
“…While the egg yolk color comes from vitellogenin whose precursor is carotenoids [ 49 ], AST also could increase egg storage time by delaying the decrease in yolk index and yolk color [ 50 ]. However, Zhu et al [ 45 ] showed that P. rhodozyma had no effect on shell thickness, Haugh unit (HU), shell strength, albumen height, and egg shape index. Meanwhile, the supplementation of AST from Haematococcus algae as much as 0.49%–0.47% which contains AST 0.35% and palm tocos into hens' diets did not affect performance or egg quality except for egg yolk color [ 47 ].…”
Section: Dietary Intake Levels Of Astaxanthinmentioning
confidence: 99%
“…various improvements in stress tolerance, innate immunity, immune-related gene expression and disease resistance). 19,22,28,73,74 The future of the global carotenoid market appears promising, which is likely to expand steadily from USD 1.5 billion in 2020 to USD 2 billion by the end of 2026, registering a compound annual growth rate (CAGR) of 4.2% during the forecast period. 75 Amongst the available carotenoids, the market is dominated by astaxanthin, shared fairly by β-carotene, lutein, lycopene and zeaxanthin, in light of their established functions.…”
Section: Natural and Synthetic Sourcesmentioning
confidence: 99%
“…Moreover, scientific efforts devoted through the years persistently substantiated the instrumental role of carotenoids in promoting animal health (e.g. various improvements in stress tolerance, innate immunity, immune‐related gene expression and disease resistance) 19,22,28,73,74 . The future of the global carotenoid market appears promising, which is likely to expand steadily from USD 1.5 billion in 2020 to USD 2 billion by the end of 2026, registering a compound annual growth rate (CAGR) of 4.2% during the forecast period 75 .…”
Section: Sources Bioavailability and Metabolism Of Carotenoidsmentioning
confidence: 99%